Characterising hydrogen induced cracking of alloy 625+ using correlative SEM - EDX and NanoSIMS. (1st April 2021) - Aboura, Y.; Martelo, D.F.; Morana, R.; Akid, R.; Moore, K.L.
Graphical abstract: Highlights: Correlative NanoSIMS and SEM-EDX was used to identify deuterium localisation in nickel alloy 625+ (UNS N07716). Local deuterium enrichments were detected at – dislocation slip bands, twin boundary and GB σ phase. Deuterium mapping analysis highlighted the synergistic role of deformation and deuterium transport during HE cracking. Abstract: Hydrogen induced cracking behaviour of O&G nickel alloy 625+ (UNS N07716) was investigated. Deuterium was introduced electrochemically into samples by cathodic polarisation (3.5 wt.% NaCl.D2 O) under different mechanical conditions. Subsequently, deuterium distributions were mapped using NanoSIMS. Deuterium was used as an isotopic tracer instead of hydrogen to avoid the detection of hydrogen artefacts. Complimentary image analysis using scanning electron microscopy (SEM) and low voltage energy dispersive X-ray (EDX) allowed the identification of microstructural features corresponding to deuterium enrichments. The results provided experimental evidence of enrichments at dislocation slip bands (DSB), twin boundary and grain boundary features that include σ precipitates.